SPATIAL AND TEMPORAL POTENTIAL OF CURRENT ENERGY AND WAVE HEIGHT IN INDONESIAN SEA - Alamsah, Azwar; Wahjudi, Ari; Moon, Park Jae; Hamidi, Nurkholis; Widhiyanuriyawan, Denny (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
The energy demand in Indonesia continues to rise, with a primary reliance on fossil fuels, leading to environmental issues such as increased CO2 emissions. To address these challenges, the exploration of renewable energy, particularly from wave and ocean current sources, becomes crucial. This research analyzes the energy potential generated from waves and ocean currents throughout Indonesia using the WAVEWATCH-III method for modeling marine data over a 10-year period. The results indicate that the energy potential from ocean currents ranges between 120-150 kW, with strategic locations around straits such as the Makassar Strait and the Java Sea. Meanwhile, the potential energy from ocean waves reaches approximately 2.5 GW over a three-month period, thanks to Indonesia's extensive coastline of 99,093 km. Spatial and temporal analyses reveal significant variations in Sea Level Anomaly (SLA) values, which can be utilized for the development of renewable energy projects. The conclusion of this research emphasizes the need for a deeper understanding of the dynamics of ocean currents and waves to maximize the utilization of renewable energy potential in Indonesia.